A Global lmmunological Observatory to meet a time of pandemics - Mina, Michael J; Metcalf, C Jessica E; McDermott, Adrian B; Douek, Daniel C; Farrar, Jeremy; Grenfell, Bryan T (eLife, 2020)
SARS-CoV-2 presents an unprecedented international challenge, but it will not be the last such threat. Here, we argue that the world needs to be much better prepared to rapidly detect, define and defeat future pandemics. We propose that a Global Immunological Observatory and associated developments in systems immunology, therapeutics and vaccine design should be at the heart of this enterprise.